Hotspots of resistance in a bordered reality. (December 2020) - Spathopoulou, Aila; Carastathis, Anna
In this paper, we examine how bordered reality is being imposed and resisted in the context of where we are placed right now, 'Greece'. Drawing on ethnographic research and discourse analysis, conducted in Lesvos, Samos, and Athens (from March to September 2016), we examine how resistance to a bordered reality took place, as islands in the north Aegean, as well as Greek and European territories, were being remapped according to the logic of the hotspot. We approach this process methodologically from the situated angle of the embodiment of resistance in the concrete experiences of people (including the researchers ourselves), whose narratives reveal the distracted spatial coordinates of the 'hotspot regime', which becomes a traveling control device. Rather than approaching the hotspots on the five Greek border islands as geographically fixed entities we introduce the concept of the mobile hotspot to show how the logic of the hotspot suffuses the uneven geographies of a bordered reality. We use the ferry as an illustrative tool with which to critically explore the density, tensions, and conflict-ridden nature of movements within, around, and against the hotspots.